Translocated native pine martens Martes martes alter short‐term space use by invasive non‐native grey squirrels Sciurus carolinensis. Issue 5 (15th March 2020) - McNicol, Catherine M.; Bavin, David; Bearhop, Stuart; Ferryman, Mark; Gill, Robin; Goodwin, Cecily E. D.; MacPherson, Jenny; Silk, Matthew J.; McDonald, Robbie A.
Abstract: Predators can shape the distributions and dynamics of their prey through direct and indirect mechanisms. Where prey animals are regarded as pests, the augmentation of predator populations might offer a potential tool in their management. Declines in invasive non‐native grey squirrel Sciurus carolinensis populations in Ireland and Scotland have been related to an increase in range and density of native pine marten Martes martes populations. These reductions in grey squirrel abundance have, in turn, been linked to recovery of native red squirrels Sciurus vulgaris . Taking the opportunity presented by a conservation translocation of pine martens from Scotland to Wales, we investigated the short‐term effects of exposure to translocated martens on the space use and survival of resident grey squirrels. Grey squirrel range size and daily distance travelled increased significantly with increasing exposure to martens but we found no effect of marten exposure on the recapture probability (i.e. apparent survival) of the sampled squirrels within the study time frame. This is suggestive of contemporary, non‐lethal effects changing the ranging or foraging regimes of squirrels, due either to predator avoidance and/or earlier lethal effects associated with a reduction in intraspecific competition. Synthesis and applications . Our evaluation mimics the conditions experienced by grey squirrels at the front edge of naturally recovering pine marten populations and presents direct evidence that pine marten translocations could play an influential role in the behaviour and dynamics of invasive non‐native grey squirrel populations. Translocations of native predators, undertaken primarily for biodiversity conservation, could therefore find additional application in managing the ecological and economic impacts of invasive non‐native prey. Abstract : Our evaluation mimics the conditions experienced by grey squirrels at the front edge of naturally recovering pine marten populations and presents direct evidence that pine marten translocations could play an influential role in the behaviour and dynamics of invasive non‐native grey squirrel populations. Translocations of native predators, undertaken primarily for biodiversity conservation, could therefore find additional application in managing the ecological and economic impacts of invasive non‐native prey. Crynodeb: Gall dosbarthiadau anifaeliad ysglafaethus newid dosbarthiad â deinamig eu hysglyfaith trwy fecanwiethiau uniongyrchol ac an‐uniongyrchol. Lle mae anifaeliaed prae yn cael eu ystyried yn bla, gall cynyddu poblogaeth anifaeliaed ysglafaethus gynnig arf i'w rheoli. Mae gostyngiadau ym mhoblogaethau anfrodorol ymledol wiwerod lwyd Sciurus carolinensis yn Iwerddon a'r Alban wedi eu cysylltiedu â chynnydd a dosbarthiad poblogaethau belaod coed Martes martes brodorol. Mae'r gostyngiad yma yn niferoedd wiwerod llwyd, yn eu tro, wedi eu cysylltu ag adferiad wiwerod goch Sciurus vulgaris brodorol. Trwy cymryd mantais o'r cyfle a gyflwynnwyd trwy trawsleoliad cadwaethol o felaod coed o'r Alban i Gymru, gwnaethom ymchwilio effeithiau tymor‐byr y belaod coed ar goroesiad a ddefnydd wiwerod llwyd preswyl o'u gynefin. Cynyddodd maint ymlediad a phellter teithiol dyddiol y wiwerod llwyd yn sylweddol ar y cyd ag amlygrwydd cynyddol belaod coed, ond ni chanfuon unrhyw effaith o amlygiad belaod ar debygolrwydd ail‐ddal (h.y. goroesiad ymddangosol) y wiwerod a samplwyd o fewn amserlen yr astudiaeth. Mae hyn yn awgrymu effeithiau cyfoes, ddi‐angheuol a fyddai'n newid cyfundrefnau chwilota bwyd neu defnydd ymestyniad cynefin. Mae hyn naill ai oherwydd mae'r wiwerod yn osgoi anifaeliad ysglafaethus neu/ac oherwydd effeithiau angheuol cynharach gysylltiedig â gostyngiad a chystadleuaeth rhwng‐rywogaethol. Synthesis a chymwysiadau . Mae ein gwerthusiad yn dynwared yr amodau a profwyd gan y wiwerod llwyd sydd ar y rheng‐flaen gyda poblogaethau belaod coed sy'n cynyddu yn naturol, ac yn cyflwyno tystiolaeth uniongyrchol bod trawsleoli belaod coed i gynefinoedd newydd yn gallu chwarae rhan ddylanwadol mewn ymddygiad a deinameg poblogaethau wiwerod llwyd estron ac ymledol. Gall trawsleoli anifaeliaed ysglafaethus brodorol a wnaethpwyd yn bennaf ar gyfer rhesymau cadwraeth bioamrywiaethol, felly ddod a gymhwysiadau ychwanegol trwy reoli effeithiau ecolegol ac economaidd rhywogaethau prae anfrodorol ac ymledol.